Aggregation of Nanochemical Microcrystals in Urine Promotes the Formation of Urinary Calculi - Yanting Lou; Wei He; Zhengyao Song (Journal of Chemistry)
With the increasing incidence and recurrence rate of urinary calculi, urinary calculi have become a serious health risk, and the research on urinary calculi has become the focus of public attention. At present, the research results on the formation mechanism of urinary calculi are not ideal, and there is no unified conclusion. In order to further study the influencing factors of the formation of urinary calculi and provide new ideas for the prevention and clinical treatment of urinary calculi, the influence of agglomeration of nanochemical microcrystals in urine on urinary calculi was studied in this paper. In this study, fresh morning urine was collected from 10 urological stone patients and 10 healthy controls without urological stone in the urology department of a hospital. After processing the experimental specimens, we first use flame atomic absorption spectrometry and alcian blue colorimetric method to detect the content of Ca2+ and citrate in the urine and then use the nanoparticle size analyzer to detect the microcrystals in the urine. Diameter, distribution, degree of aggregation and potential, and finally HRTEM observation to observe the morphology, chemical composition, and element composition of the nanocrystals. The results showed that the content of Ca2+ and lemon hydrochloric acid in the urine of the experimental group was lower than that of the control group. The particle size of the nanocrystals increased with the increase in the pore size of the membrane. The average particle size of the experimental group increased gradually from 163 ± 31 nm to 3219 ± 863 nm, while the average particle size of the control group increased from 183 ± 65 nm to 997 ± 522 nm. The mean value of the potential decreased with the increase in the pore size of the filter membrane. The change amplitude of the experimental group was 6.57 mV, while the change amplitude of the control group was only 1.75 mV. In the composition of nanocrystals, element O accounts for the most, accounting for 42.54% of all elements. This indicates that the aggregation of nanocrystals in urine will lead to the rapid increase in the size of nanocrystals, which will eventually lead to the formation of stones.